Exploring the Sadharanikaran Model of Communication from a Health Communication Perspective - Khadka , Upendra (Bodhi: An Interdisciplinary Journal, 2024)
This article explores Adhikary’s Sadharanikaran Model of Communication (SMC) from a health communication perspective. The article has been divided into three sections. In the first section, an overview of the SMC is presented followed by a discussion on health communication in the second section. The final section of this article is devoted to explore the relationship between healthcommunication and the SMC.